Analisis Kemampuan Pemahaman Konsep Matematika Siswa Berbantuan Media Schoology - Yulianah, Lia; Ni'mah, Khomsatun; Rahayu, Diar Veni (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2020)
The purpose of this study was to examine the mathematical concepts of students in solving the problem of polyhedron of cubes and cuboids with assisted of Schoology media. This research uses qualitative methods with descriptive approach. This study describes the ability to understand mathematical concepts that owned of students with Schoology media. Research subjects is three students selected by purposive sampling based on conditions and situations that occured during the current co-19 pandemic. The data collection used consists of tests of understanding the ability of mathematical concepts. Based on the results of research showed that the ability to understanding students' of mathematical concepts with Schoology-assisted able to provide understanding of material polyhedron of cubes and cuboids by the average results of students getting value 91,67. Where the first student is able to reach an understanding indicator of mathematical concepts from given by agreeing to the concept, classifying objects according to certain properties, giving concepts in various forms of mathematical representation, explaining the relationship between one concept with another concept, and applying the concept in problem solving . While the second and third students can only reach four indicators from the second indicator given. Nevertheless, students show positive responses to Schoology media.Â Keywords: Understanding Mathematical Concepts, Schoology Media